EFEKTIVITAS PENGEMBANGAN USAHA KECIL DAN MENENGAH DALAM PANDANGAN HUKUM SYARIAH DI ACEH - Asniah, Asniah (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
The effectiveness of developing small and medium enterprises in the view of sharia law in Aceh is an important topic in regional economic development. Based on research conducted, there are several factors that threaten the effectiveness of small and medium enterprise development in Aceh, such as difficult access to capital sources, minimal product innovation, less than optimal marketing, and inadequate workforce. The aim of this research is to determine and explain the development of small and medium enterprises from the perspective of sharia law in Aceh. The type of research used in this research is field research with a descriptive qualitative approach, to obtain data using interview and observation techniques, then the collected data is analyzed by data reduction, data analysis and drawing conclusions. The results show that the effectiveness of developing small and medium enterprises in the view of sharia law in Aceh relating to the provision of sharia financing capital shows that sharia microfinancing can help increase the productivity and income of small and medium enterprises and sharia microfinancing can help increase capital, turnover and profits of small businesses medium in Aceh so that sharia microfinancing can be an effective tool in developing micro, small and medium enterprises in Aceh and can reduce poverty and prevent unemployment.